Strange bedfellows - Ries, Ariel Slamet (HarperAlley, an imprint of HarperCollinsPublishers, 2025)
"In the not-too-distant future, most of humanity resides on its last-ditch effort at utopia: Meridian, a remote alien planet where you're more likely to be born superhuman than left-handed. None of that is important to Oberon Afolayan. Since his mildly public breakdown, his whole life seems to be spiraling out of control--from dropping out of university to breaking up with his boyfriend, it seems like only a karmic inevitability when he wakes up one day with the ability to conjure his dreams in the real world. Oberon's newfound powers come with a facsimile of his high school crush, Kon, who mysteriously dropped off the face of the planet almost three years ago and who is a little more infuriating (if not also infuriatingly hot) than Oberon remembers. Kon makes it his mission to turn Oberon's life around, and while they struggle to get a handle on his powers and his disastrous personal life (not to mention the appearance of strange nightmare creatures), it turns out this dream version of Kon has secrets of his own--dangerous ones. Oberon might have more on his plate than he originally thought, but is giving up his dreams--even the one he might have accidentally fallen in love with--the only way to find happiness in reality?"--Provided by publisher.